Meaning in life and smartphone addiction among Chinese female college students: The mediating role of school adjustment and the moderating role of grade - Zhao, Hao; Rafik-Galea, Shameem; Fitriana, Mimi; Song, Tianjiao (Frontiers in Psychology, 2023)
Background The fact that female college students are more addicted to smartphones than male college students has raised public concerns. However, previous studies have rarely explored the mechanism of female college students’ smartphone addiction. Previous studies have shown that identity may affect the formation process of female college students’ smartphone addiction, and the identity of female college students in different grades may be different. Nonetheless, few studies have explored the grade differences in the formation process of female college students’ smartphone addiction. Methods The present study examined the relationship between meaning in life, school adjustment, and smartphone addiction among Chinese female college students using a moderated mediation model in which school adjustment played a mediating role and grade played a moderating role. A total of 1,076 Chinese female college students (Age: 19.83 ± 1.11; 369 freshmen, 379 sophomores, and 328 juniors) completed an online questionnaire regarding meaning in life, school adjustment, and smartphone addiction. Results (1) School adjustment mediated the relationship between meaning in life and smartphone addiction. (2) School adjustment had a partial mediating effect between meaning in life and smartphone addiction for female freshmen and sophomores, but it did not exist among female juniors. (3) The influence of school adjustment on female sophomores’ smartphone addiction was significantly stronger than that of female freshmen. Conclusion The findings of this study advance our understanding of the potential impacts of meaning in life on smartphone addiction and provide a grade perspective for targeted prevention or intervention with female college students’ smartphone addiction.